Exploring the Socio-economic Realities of Shatranji Workers in Rangpur - Faruque, Omar (Asian Business Review, 2024)
The Shatranji industry in Rangpur, Bangladesh, is a vital traditional craft and a Geographical Indication (GI) product, supporting around 50,000 families. This study examines the socio-economic conditions of Shatranji workers based on a qualitative survey of 115 workers, all of whom are women. The findings reveal that most workers are 30–40 years old, have limited education, and belong to low-income families. They earn modest wages, with the majority earning less than 100 takas daily, and live in poor housing conditions. Financial insecurity is widespread, with 67% of workers lacking savings or loans. Despite these challenges, there is a strong emphasis on education for their children. Unemployment rates within families are high, yet workers generally perceive their workplaces as safe. However, improvements in living conditions have been minimal, and nutritional intake remains inadequate. The study highlights the need for targeted interventions, including wage increases, job security, improved healthcare, and financial literacy programs. These recommendations aim to enhance the socio-economic status of Shatranji workers and ensure the sustainability of this culturally significant industry.